A Retrospective Study of Fetal Congenital Anomalies In Tertiary Care Hospital - Gosavi, Manasi; Deshpande, K M; Mynarova, Aneta; Ratnakar, Ashwini (Journal of Neonatal Surgery, 2025)
Background: Congenital anomalies are a significant cause of fetal morbidity and mortality. Fetal autopsy remains the gold standard for confirming congenital malformations and assessing recurrence risk. Methods: A retrospective review was conducted on fetal autopsy at a tertiary care hospital over a defined period. Cases with confirmed congenital anomalies were analysed for prevalence, type of anomaly and associated clinical details. Anomalies were categorized system-wise to identify the most commonly affected systems. Results: Out of 264 fetal autopsies examined, congenital anomalies were observed in 100 cases (37%). Central nervous system malformations were the most prevalent, followed by musculoskeletal, cardiovascular, and renal anomalies. Multiple system involvement was also noted. Conclusion: Fetal autopsy pathology is crucial for accurate diagnosis, guiding genetic counseling and preventing recurrence through targeted interventions and improved antenatal care.